Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.1210/jcem.85.5.6584
|View full text |Cite
|
Sign up to set email alerts
|

Pamidronate Treatment of Severe Osteogenesis Imperfecta in Children under 3 Years of Age*

Abstract: Severe osteogenesis imperfecta (OI) is a hereditary disorder characterized by increased bone fragility and progressive bone deformity. Cyclical pamidronate infusions improve clinical outcome in children older than 3 yr of age with severe OI. Because earlier treatment may have potential to prevent deformities and improve functional prognosis in young children, we studied nine severely affected OI patients under 2 yr of age (2.3-20.7 months at entry) for a period of 12 months. Pamidronate was administered i.v. i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
118
1
14

Year Published

2002
2002
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 134 publications
(139 citation statements)
references
References 12 publications
6
118
1
14
Order By: Relevance
“…Similar results have also been seen in several uncontrolled trials reporting a reduction in (bone) pain [45,46,47,48]. However, our results in children deviated from the review of Dwan et al [39] in which a reduction in bone pain was found in merely 1 out of 6 studies; however, they included adult studies and studies comparing different doses of BP without control groups [39].…”
Section: Discussionsupporting
confidence: 75%
“…Similar results have also been seen in several uncontrolled trials reporting a reduction in (bone) pain [45,46,47,48]. However, our results in children deviated from the review of Dwan et al [39] in which a reduction in bone pain was found in merely 1 out of 6 studies; however, they included adult studies and studies comparing different doses of BP without control groups [39].…”
Section: Discussionsupporting
confidence: 75%
“…The effect of this on bone fragility is not known. Reassuringly, at least in the paediatric population with OI, IV pamidronate can decrease fracture incidence [6,12,33,34], and a reduction in fracture has also been observed with oral bisphosphonates in some [13,27,35] but not all [14,15,36] studies. There have been only two controlled trials of bisphosphonates in adults with OI type I.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with severe OI have numerous painful fractures, progressive skeletal deformities, and retarded bone growth, resulting in short stature (15)(16)(17). There is no cure for OI, and only one class of drugs, the bisphosphonates, has shown therapeutic potential (18)(19)(20). We previously demonstrated the feasibility of allogeneic bone marrow transplantation (BMT) for children with severe OI (21).…”
mentioning
confidence: 99%